Power's Promise : Electricity Reforms in Eastern Europe and Central Asia - Lampietti, Julian (Washington, DC: World Bank, 2013)
This study analyzes the fiscal, efficiency, social, and environmental impact of power sector reforms in seven countries in the ECA region. It finds sector deficits have been falling over the last decade and that the savings from lower sector deficits did not translate into higher social spending. More emphasis must be placed on monitoring deficits and tailoring policy reform to country specific circumstances. The impact of reform on utility efficiency, as measured by the cost of generation, system loss collections, and operational efficiency, is ambiguous. While overall revenue per kilowatt hour increased in almost all countries, problems continue with losses, collection rates, and staffing. In terms of social impacts, electricity spending as a share of income increased, especially for the poor, while consumption stayed the same. In terms of environmental impacts, reforms did slightly improve energy efficiency in power plants though this has little direct impact on human health because the electricity sector's share of the total health damage from air pollution is negligible. Several lessons emerge from the analysis. Undertaking simple ex ante simulations of reform impacts will allow better identification of potential reform benefits and costs. Placing more emphasis on outcome-based indicators of service quality would help ensure that future operations produce the intended end-user benefits. In many cases, tariff increases can and should be explicitly timed to coincide with service quality improvements. Yet, this may not be always possible. Where it is not, the adverse impact of tariff increases, especially for low-income consumers, should be mitigated by improving access to and efficiency in the use of clean alternatives.